EKSTRAKSI DAUN PELAWAN (Tristaniopsis merguensis)SEBAGAI ANTIOKSIDAN MENGGUNAKAN MICROWAVE ASSISTED EXTRACTION (MAE) - Sito Enggiwanto; Fusfita Istiqomah; Kasro Daniati; Occa Roanisca; Robby Gus Mahardika (Indonesian Journal of Pure and Applied Chemistry, 2018)
Indonesia is a country that produces a wealth of abundant biodiversity, one of which is a plant that is often cultivated the tree of Pelawan (Tristaniopsis merguensis). Pelawan trees are widely spread in Indonesia one of them found in the forests of the Bangka Belitung island. Therefore, this study aims to identify the secondary metabolites and testing antioxidants in leaf of pelawan extract by comparing methods of Microwave Assisted Extraction (MAE) with maceration method. The resistant leaf used in this study was obtained from Sempan, Bangka Belitung. The observation result shows that the use of MAE method can extract with faster time compared with maceration method. So the MAE method is more effective than the maceration method. The using of MAE method for 30 minutes obtained the highest yield percentage of 41.3% in ethanol solvent which is more effective than acetone solvent. Extraction by using 48 hour maceration yields is 28.985%. While the extraction with 30 minute maceration is 13.385%. Testing of antioxidant activity using Microwave Assisted Extraction (MAE) method on acetone solvent has the highest antioxidant activity than ethanol extract that is 9,501 μg/mL. The use of the MAE method is more efficient in extracting the leaves of Pelawan than the maceration method when viewed from the time and antioxidant activity.